Yaothrips as a new synonym of Pezothrips, with description of the male of Pezothrips pediculae comb.n. (Thysanoptera: Thripidae) - Tong, Xiaoli; Liu, Liangxin (Zootaxa, 2019)
The genus Yaothrips was erected by Mirab-balou et al. (2011a) based on four micropterous females of a new species, Y. shii, from China, Tibet. Subsequently, Mirab-balou et al. (2015) transferred to the genus Yaothrips a further species described from Tibet, Taeniothrips pediculae Han that had been based on two micropterous females. Moreover, these authors placed Y. shii as a new synonym of Y. pediculae. Mirab-balou et al. (2011b) also described as a new species from Tibet Pezothrips brunicornis, based on macropterae of both sexes. Recently we examined a collection of Y. pediculae from the Qinghai-Tibet Plateau, China, and this included two specimens of the previously unknown male. We studied the type specimens of P. brunicornis and found that the males of Y. pediculae and P. brunicornis are very similar. In particular, abdominal tergite IX bears a pair of short stout setae medially (Figs 7–8) and sternites III–VII have small scattered pore plates (Figs 5,9). Considering the similarities, the genus Yaothrips is here synonymized with Pezothrips,